Pengukuran Kinerja Bank Perkreditan Rakyat Werdhi Sedana Kabupaten Gianyar Dengan Teknik Balanced Scorecard - Andira Sari, Pande Made Hierra; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2019)
This research was conducted at BPR Werdhi Sedana from 2015 - 2017. The population is all employees and customers of BPR Werdhi Sedana. The sample for employees was 41 and the samples for customers used were 99 savings customers, 87 deposit customers and 96 credit customers. The technique used to take samples is simple random sampling.. The data analysis technique used is perspective on the Balanced Scorecard. The financial perspective got results that are categorized as good. The customer perspective can increase customer satisfaction that produces good numbers and is supported by an increase in the number of customers. The internal business perspective uses infrastructure capacity which has decreased and on innovation growth, BPR has been able to increase innovation in 2018. Then, the learning and growth perspective shows an increase in employee productivity and employee satisfaction. Keywords : Performance assessment , balance scorecard.